Effects of corneoscleral topography on soft contact lens performance: A pilot study. Issue 6 (December 2018) - Tan, Bo; Zhou, Yixiu; Graham, Andrew D.; Lin, Meng C.
Highlights: Corneoscleral junction (CSJ) is quantified with an unique matrix. Significant differences of CSJ are found among quadrants and ethnic groups. The deepest CSJ profile and/or most irregular CSJ surface are found in the nasal quadrant. Caucasians have deeper and/or more irregular CSJ than do Asians and Latinos. The less vertical CSJ heterogeneity, the more comfortable soft contact lens wear. Abstract: To quantify corneoscleral junction (CSJ) topography in soft contact lens (SCL) wearers, and assess the association between the CSJ and SCL performance and subjective comfort, forty-four adapted SCL wearers (16 Asians, 16 Caucasians, 12 Latinos) were recruited for the present study. Corneal topography was taken with a Medmont E300 (Medmont International, Pty Ltd.). CSJ images were taken with a commercial OCT (Bioptigen, Inc.). Our published CSJ image analysis technique was used to describe the geometric properties of the CSJ using the sum of squared orthogonalized residuals (SSRo). Multivariable mixed effects models were employed to examine associations between SSRo and subject demographics, ocular characteristics, SCL fit and performance, and comfort. The SSRo was significantly related to quadrant (p < 0.001), ethnicity (p = 0.014), and horizontal corneal shape factor (p = 0.044). The nasal quadrant had the largest SSRo, indicating the steepest CSJ profile and/or the most irregular CSJ surface, followed by the inferior quadrant. The superior and temporal quadrants had the smallest SSRo, indicating relatively flat and even CSJ topography. Caucasians had the steepest and/or most irregular CSJ compared with Latinos and Asians. Less inferior-superior heterogeneity in the SSRo was associated with greater comfort after 6 h of lens wear. The SSRo was proved to be a useful tool to quantify CSJ geometry in SCL wearers. Significant differences in the SSRo were found among quadrants and ethnic groups. Better subjective comfort after 6 h of SCL wear was associated with a smaller difference in the SSRo between the superior and inferior quadrants.